Therapeutic Communication Competence in Active Listening, Empathy, and Relationship Initiation among Indonesian Nursing Students: A Cross-Sectional Analysis of Role-Play and Peer Simulation-Based Learning Outcomes - Maria Susila Sumartiningsih (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Therapeutic communication competence, encompassing active listening, empathy, relationship initiation, information gathering, and interaction closure, is foundational to safe and effective nursing practice. Despite its centrality in nursing education, evidence on competence levels achievable through simulation-based learning prior to clinical exposure remains limited, particularly in Indonesian contexts. Objective: Grounded in Peplau's Interpersonal Relations Theory and Kolb's Experiential Learning Theory, this study assessed therapeutic communication competence levels and examined associations between simulation participation and competence outcomes among first-semester nursing students. Methods: A cross-sectional descriptive design was employed with 48 first-semester nursing students (total sampling) completing a 14-week Nursing Communication course at Institut Tarumanagara, Jakarta. The culturally adapted Therapeutic Communication Skills Scale–Indonesian Version (TCSS-25; CVI = 0.89, α = 0.86) measured four competence domains. Chi-square tests and Pearson correlations examined associations between role-play participation and competence levels. Results: More than half (58.3%) achieved good competence (mean = 72.8%, SD = 12.4). Active listening and empathy scored highest (76.8%), while closing therapeutic interactions scored lowest (68.5%). Role-play participation significantly predicted competence levels (χ² = 8.92, p = 0.01, Cramér's V = 0.43). Demographic variables showed no significant associations. Conclusion: Simulation-based learning effectively develops therapeutic communication competence in preclinical nursing students; however, the 41.7% who did not achieve good competence warrant targeted interventions, particularly in structured closure skills training and increased role-play engagement.